A Study on the Psychosocial Predictors of Cardiovascular Diseases: The Major Role of Forgiveness (Medical Forum Monthly, 2021)
Objective: to determine the dimension of forgiveness in Cardiovascular patients and compare them with the normals (without any Cardiovascular history).Study Design: Cross-sectional comparative studyPlace and Duration of Study: This study was conducted at the OPD, Department of Cardiology, Rehman Medical Institute (RMI) from Oct to Dec 2020, Peshawar and Jan to Feb 2021 from twin cities of Rawalpindi and Islamabad.Materials and Methods: The study was done on a total sample of 163 comprising both cardiovascular heart patients and the normals. Informed consent was obtained from all the participants. A questionnaire was designed and based on translated version of Transgression Related Interpersonal Motivations Inventory (TRIM-18) as developed by McCullough, Root and Cohen in 20061. Data was analyzed using IBM SPSS Version 23. An independent samples t-tests was used for statistical significance.Results: The results of the study revealed that there is statistically significant difference between the patients and the normals groups on the dimensions of forgiveness. Patients were high in the unforgiveness and low on forgiveness dimension than the normals.Conclusion: The study concludes that for the effective management of the cardiovascular patients both psychosocial and medical factors should be carefully weighed and assessed in different patients depending on the severity of their disease.